(untitled) (Fiep Bulletin - online, 2014)
This study it has as objective to raise perspectives on the process of evaluation in the practical one of the Brazilian university formation, standing out the identity conservative who the evaluation, while process, presents until the present. The indifference stops with the evaluation system can be attributed and be appended to the practical connotation that it is defended by many professors for the graduation courses, being able to be they in level of bachelor and/or licentiate. Therefore, they are not only the practical formal and informal to evaluation and its consequences that can interest a sociology of the evaluation in Physical Education, but also the molds that they involve, or not, the professors.